Effects of short-term detraining on measures of obesity and glucose tolerance in elite athletes - Liu, T. C.; Liu, Y. Y.; Lee, S. D.; Huang, C. H.; Chien, K. Y.; Cheng, I. S.; Lin, C. Y.; Kuo, C. H. (Journal of Sports Sciences, 2008)
Athletes frequently adjust their training volume in line with their athletic competition schedule, onset of sport injury, and retirement. Whether maintenance of partial training activity during the detraining period can preserve optimal body composition and insulin sensitivity is currently unknown. Sixteen elite kayak athletes (mean VO2max: 58.5 ml · kg-1· min-1, s = 1.77) were randomly assigned to a totally detrained group (age: 20.8 years, s = 0.7; body mass index: 23.74, s = 0.54) or partially detrained group (age: 21.8 years, s = 0.7; body mass index: 23.20, s = 1.02), whereby totally detrained participants terminated their training routine completely and the partially detrained participants preserved ~50% of their previous training duration with equivalent intensity for one month. Body mass, waist circumference, oral glucose tolerance test, insulin, leptin, cortisol, and testosterone were measured during the trained state and after detraining. Waist circumferences for both the partially detrained and totally detrained groups were significantly elevated after detraining, with no group difference. However, body mass was reduced in both groups. Significant elevations in the area under the curve for insulin and fasted leptin with detraining were observed. These changes were greater in the totally detrained participants. In conclusion, the present results show that maintaining partial training activity cannot prevent an increase in waist circumference. During the detraining period, the magnitude of increase in plasma insulin and leptin concentrations was regulated in an activity-dependent manner.